Evaluating Singapore’s CHAT Assessment Service by the World Mental Health Organisation (WHO) “Youth-Friendly” Health Services Framework - Lee, Yi Ping; Ngaiman, Nur Khairunisa Binte; Poon, Lye Yin; Abdul Jalil, Hanisah Binte; Yap, Ming Hui; Abdin, Edimansyah; Subramaniam, Mythily; Lee, Helen; Verma, Swapna K. (Frontiers in Psychiatry, 2019)
Young people experience high rates of mental health issues. However, many do not seek professional help. In order to encourage help-seeking behavior among young people, it is important to ensure that services are youth-friendly. This study aims to evaluate the Community Health Assessment Team (CHAT)'s mental health assessment service model using the World Health Organization (WHO) youth-friendly health service framework of accessibility, acceptability and appropriateness (AAA), and to ascertain the extent to which the CHAT service model is youth-friendly. Three hundred young people aged 16 to 30 years, who had gone through CHAT mental health assessments completed a 27-item questionnaire. Majority rated the items in the questionnaire favorably. Our results suggest that majority of the young people who accessed CHAT mental health assessment service found it to be youth friendly.